PELAKSANAAN GOOD GOVERNANCE OLEH SATGAS KOMUNITAS KAMPUNG PERLINDUNGAN PEREMPUAN DAN ANAK (DULREMPAK) KOTA DUMAI TAHUN 2023 - Ahmad, Rudi Purwana; ,, Wazni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Good governance is an absolute necessity for the majority of the people in order to create a political system of government that is more in favor of the people's interests in accordance with universal democratic principles. This study discusses the Implementation of Good Governance by the Task Force for the Protection of Women and Children Village Community (DULREMPAK) of Dumai City. The purpose of this study is to describe the Implementation of Good Governance by the Task Force for the Protection of Women and Children Village Community (DULREMPAK) of Dumai City. The theory used in this study is Good Governance according to the Indonesian Transparency Society (MTI) in Amir Faisol (2006). This study uses a qualitative method with data collection techniques using Interview Techniques and Literature Study. For data sources for the Implementation of Good Governance by the Task Force for the Protection of Women and Children Village Community (DULREMPAK) of Dumai City, a descriptive qualitative research approach is used. The results of the study explain that the Implementation of Good Governance by the Task Force for the Protection of Women and Children Village Community (DULREMPAK) of Dumai City uses 6 (six) indicators, namely, community participation, rule of law, transparency, justice, effectiveness and accountability. Even though there are still several obstacles in terms of budget, implementation and human resources, the Dumai City Women and Children Protection Community is able to realize several indicators of Good Governance. Kata Kunci:Pelaksanaan,Good Governance,